2021
DOI: 10.1021/acs.macromol.1c01382
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Architectures Can Alter the Dynamics of Polymer–Nanoparticle Composites

Abstract: Polymer nanocomposites exhibit remarkable physical properties that are attractive for many applications. These systems have been so far investigated using linear polymer chains; the role of polymer matrix architecture in local dynamics, bulk rheology, and nanoparticle (NP) motion remains unexplored. Here, using quasi-elastic neutron scattering, bulk rheology, and Xray photon correlation spectroscopy, we investigated nanocomposites with spherical silica nanoparticles well dispersed in poly(ethylene oxide) matri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
(82 reference statements)
0
6
0
Order By: Relevance
“…Here, β is the stretching exponent and τ is the relaxation time. A delta function and a constant background were also added to account for possible residual immobile fractions and very fast localized motions. , The fitted curves are shown as solid lines on the spectra (note that the elementary Rouse rates for the neat polymers except for HBG6 were reported in our previous work). It was found that β is very close to 0.5 for all samples, confirming that dynamics is due to the curvilinear multimodal motion of the segments along the backbone (i.e., Rouse motion).…”
Section: Resultsmentioning
confidence: 99%
“…Here, β is the stretching exponent and τ is the relaxation time. A delta function and a constant background were also added to account for possible residual immobile fractions and very fast localized motions. , The fitted curves are shown as solid lines on the spectra (note that the elementary Rouse rates for the neat polymers except for HBG6 were reported in our previous work). It was found that β is very close to 0.5 for all samples, confirming that dynamics is due to the curvilinear multimodal motion of the segments along the backbone (i.e., Rouse motion).…”
Section: Resultsmentioning
confidence: 99%
“…Polymer nanocomposites (PNCs) with tunable and superior properties are crucial for the development of advanced technologies [ 1 ]. Polymer chains and nanoparticles interact at varying strength and length scales and control the thermo-mechanical properties of PNCs [ 2 4 ]. Regarding the nanoparticles (NPs), their chemistry, size, concentration, shape, and state of dispersion play a critical role in the final properties of polymer-nanoparticle composite systems [ 4 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Polymer chains and nanoparticles interact at varying strength and length scales and control the thermo-mechanical properties of PNCs [ 2 4 ]. Regarding the nanoparticles (NPs), their chemistry, size, concentration, shape, and state of dispersion play a critical role in the final properties of polymer-nanoparticle composite systems [ 4 7 ]. On the polymer side, molecular weight, chain rigidity, segment packing density, grafting density, and chemical and dynamical heterogeneity are known to influence the local and bulk rheological properties of PNCs [ 2 , 4 , 8 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations